Progressive Spread of Beta-amyloid Pathology in an Olfactory-driven Amyloid Precursor Protein Mouse Model. (15th April 2023) - Murray, Helen C.; Saar, Galit; Bai, Li; Bouraoud, Nadia; Dodd, Stephen; Highet, Blake; Ryan, Brigid; Curtis, Maurice A.; Koretsky, Alan; Belluscio, Leonardo
Highlights: Spread of human β-amyloid protein from olfactory epithelium to the olfactory bulb in OMP-hAPP mice. Reduced olfactory bulb volume in OMP-hAPP mice due to APP-mediated disruption of development. Progressive accumulation of human β-amyloid protein in the piriform cortex and hippocampus of OMP-hAPP mice. β-amyloid deposition was not accompanied by regional atrophy in OMP-hAPP mice. Abstract: Years before Alzheimer's disease (AD) is diagnosed, patients experience an impaired sense of smell, and β-amyloid plaques accumulate within the olfactory mucosa and olfactory bulb (OB). The olfactory vector hypothesis proposes that external agents cause β-amyloid to aggregate and spread from the OB to connected downstream brain regions. To reproduce the slow accumulation of β-amyloid that occurs in human AD, we investigated the progressive accumulation of β-amyloid across the brain using a conditional mouse model that overexpresses a humanized mutant form of the amyloid precursor protein (hAPP) in olfactory sensory neurons. Using design-based stereology, we show the progressive accumulation of β-amyloid plaques within the OB and cortical olfactory regions with age. We also observe reduced OB volumes in these mice when hAPP expression begins prior-to but not post-weaning which we tracked using manganese-enhanced MRI. We therefore conclude that the reduced OB volume does not represent progressive degeneration but rather disrupted OB development. Overall, our data demonstrate that hAPP expression in the olfactory epithelium can lead to the accumulation and spread of β-amyloid through the olfactory system into the hippocampus, consistent with an olfactory system role in the early stages of β-amyloid-related AD progression.